Educación Matemática: Escenario e ideas para una nueva disciplina (ING) - Ruiz, Ángel; Chavarría, Jesennia (Uniciencia, 2003)
We examine Mathematics Education in the current historical scenario, its recent stages of development and the main theoretical trends we identify it has. A special emphasis is given to the theoretical foundations of this a new academic and scientific discipline. From this analytical exercise we will outline the most important historical and theoretical characteristics of this discipline for the years to come.